Embryonic and early development of the Zagros tooth‐carp, Aphanius vladykovi (Actinopterygii: Cyprinodontidae). (21st February 2018) - Sanjarani Vahed, Nafiseh; Esmaeili, Hamid Reza; Masoudi, Mojtaba; Ebrahimi, Mehregan
Abstract: The embryonic and early larval development of laboratory reared Zagros tooth‐carp, Aphanius vladykovi Coad, 1988, are described and illustrated. Development and embryogenesis start with the external fertilization of sticky, transparent and spherical telolecithal/macrolecithal eggs with a mean diameter of 1.61± 0.12 mm and it continues with meroblastic/radial cleavage, blastulation/blastula formation, epibolic cell migration during gastrulation and organogenesis resulting in a newly hatched larvae of 5.23 ± 0.09 mm in length with attached yolk sac at about 164 hr (at 24 ± 1°C) after fertilization. Abstract : In this study, we have demonstrated that A. vladykovi embryos can be successfully reared in the laboratory and have provided a detailed description of embryonic development including zygote, blastula, gastrula, organogenesis, and early larvae. Understanding of its embryonic stages and development will help in use of techniques to increase its population. By providing such data, we can plan for its artificial propagation to restock it in its natural habitats and to establish gene banks.